Peran Orang Tua Anak Usia 3-7 tahun Terhadap Pentingnya Olahraga Renang - Sandy, Ricky Ari; Paryadi, Paryadi; Jupri, Jupri; Makmun, Makmun; Satriana, Malpaleni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to find out what role parents play in the importance of swimming for children aged 3-7 years in the city of Samarinda. This research uses a qualitative method with focused interviews and a data collection method using a questionnaire. The research population is parents in the city of Samarinda. The sample was taken using incidental sampling, totaling 28 people. Interview transcripts were not directly analyzed, but used open coding and axial coding. Qualitative data analysis procedures use techniques. The results of the analysis of interview data with 28 participants in this research show that all of them have an important role as parents in supporting their children's swimming sports activities. The roles in the context of this research are the role of facilitator, role of motivator, and role of mentor. These roles are carried out optimally by participants so that they can lead their children to the swimming sports goals that have been agreed upon with their swimming coach. In conclusion, the role of parents in supporting the child's swimming training process and the role of parents has a very good impact. From the research results it was found that there are 3 important roles of parents, namely, the role of facilitator, the role as motivator, and the role of guide Keyword: Early Childhood, Parental Role, Swimming Sport,